LIVER DYSFUNCTION AND DENGUE SHOCK SYNDROME:A CLINICAL AND LABORATORY STUDY OF PEDIATRIC DENGUE PATIENTS - MEHTA, ANITA; Pandit, Abha (Innovare Journal of Medical Sciences, 2017)
ABSTRACT Background & aim:Availability of practical simple early indicators of worsening risk of dengue infection in pediatric patients would serve alert for monitoring and timely fluid replacement to avert the shock syndrome. Liver involvement in dengue shock syndrome(DSS) is known, hence role of serum liver enzyme monitoring as practical predictor of risk of DSS was investigated Method:50 DSS and 63 non-DSSÂ pediatric dengue patients were compared on clinic laboratory parameters at admission to draw relevant distinctions . Result:DSS patients were distinguished by frequent complaint of abdominal pain,hepatomegaly,elevated hematocrit and serum aspartate transaminase levels relative to non-DSS cases. Conclusion:Regular serum liver enzyme monitoring is suggested as worthwhile for predicting patients at greater risk of developing DSS.Close monitoring of shock and timely fluid replacement in such patients should improve outcome. Keywords: Aspartate amino transferase; Dengue shock syndrome; Liver dysfunction. Â Â